Penamaan Perahu di Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan: Sebuah Kajian Antropolinguistik - Satrio Satrio; Fajri Usman; Oktavianus Oktavianus (Center of Language and Cultural Studies, 2021)
This study is an attempt to examine the names of the boats and the categorization of boat names in Linggo Sari Baganti Subdistrict, Pesisir Selatan Regency. The study of boat names is also associated with the function, meaning, and cultural values ​​contained in these names. The purpose of this study is to describe and explain the categorization and naming process of boats. Describe and explain the function, meaning, and cultural value of the names of the boats. Based on the results of data analysis, 60 (sixty) boat names were categorized in the names of fruits, animal names, names of children, naming events, naming conditions, and place names. The boat names given can distinguish self-identity for boat owners. The name of the boat given is very valuable, valuable, and useful, and contains good meaning. The function of the name of the boat, there are five functions, namely (1) information function, (2) expressive function, (3) directive function, (4) aesthetic function, and (5) fatigue function. The meaning contained in the name of the boat there is three meanings, namely (1) the meaning of the futurative name, (2) the meaning of the name of the situation, (3) the meaning of the name of the memory. The cultural values ​​contained in the names of the boats. Namely the value of social welfare, the value of hard work, the value of discipline, the value of commitment, the value of social solidarity, the value of cultural preservation and creativity, the value of gender management, the value of peace, the value of harmony and resolution of conflict, and the value of gratitude.